Understanding an Unique Presentation of Gridhrasi and its Management through a Special Treatment Protocol - A Case Report - Sweta Tyagi,; D Achyut Bharadwaj,; Dhyan Surendranath, (AYUSHDHARA, 2023)
One of the most prevalent Vata illnesses, Gridhrasi shares many characteristics with sciatica, including pain or discomfort along the sciatic nerve. Here is a case of Gridrasi/sciatica which has a very unique presentation different from the typical presentation of pain, radiating from the lower back to the feet. Though multiple treatment modalities haven been on the rise for the treatment of Gradhrasi/Sciatica, there is a lacuna for a specific treatment protocol which covers the disease treatment in its entirety and hence this effort standardises a protocol for the same. Aim and Objectives: The aim of this study was to document this unique presentation of Gridrasi/ Sciatica and to access the efficacy of Ayurvedic management with a specific treatment protocol in Gridhrasi. Materials and Methods: It is a single case study. A 55 year old man complaining of pain originating from the left heel, radiating to the lower back, correlated with Gridhrasi of left leg since 2 months approached to Ayurvedic hospital and a treatment protocol which includes Siravyadha, Sadhyovirechana, Kala Basti, Choorna Pinda Sweda, Kati Basti, Kati Bandha and Snighda Agnikarma was given. The treatment protocol was continued for a period of 11 days. Results: Symptomatic assessment of patient was carried out after eleven days and satisfactory outcome was observed and overall quality of life of patient was significantly improved. Conclusion: The aforementioned treatment protocol gives a significant relief for the management of even this unique presentation of Gridrasi/Sciatica.